The Impact of the Information Society on the Legal Paradigm: on the Actualization of the Scope and Form of the Category - Feltsan, Ivan (Problems of legality, 2026)
Abstract The purpose of the article is to determine the impact of the information society on the scope and form of the category of the “legal paradigm.” To achieve this aim, the research applies a jurisprudential methodology conceptualized as the result of a discourse combining doctrinal-ideological, strategic, and instrumental components. The doctrinal-ideological basis of the study is the communicative approach. The strategic basis lies in the heuristic potential of the axiological approach. The instrumental component of the research methodology consists of general scientific and specialized methods and techniques of scientific cognition. The article reveals the potential of the jurisprudential paradigm as an integrated complex encompassing legal education, legal science, and legal practice. A reconceptualized understanding of the jurisprudential paradigm as an updated form and scope of the category of the “legal paradigm” is proposed. In the modern world, various models exist for addressing hierarchical relationships in the system of legal education, science, and practice. The obtained research results aim to: 1) substantiate the importance of developing interdisciplinarity and integrativeness in legal scientific knowledge; 2) demonstrate the necessity of perceiving the jurisprudential paradigm as a system that includes legal science, education, and practice; 3) engage additional resources of the academic legal community in developing practical foundations for implementing interdisciplinarity and integrativeness in scientific knowledge.